Accessing the field: Disability and the research process - Brown, Lindsey; Boardman, Felicity K. (Social science & medicine (1982), 2011)
Disability is as much a factor in interactional dynamics as ethnicity, age, gender or sexuality, and therefore its impact on the processes around qualitative research warrants much more systematic attention. Disabled researchers are not confined to disability studies research, although most accounts of the impact of disability on the research process have, thus far, been undertaken within this field. This paper moves beyond this narrow focus to consider the impact of disabled identities and the embodied experiences of impairment on studies involving, primarily, non-disabled people. By reflecting on our experiences as visibly disabled researchers, we highlight some of the practical, ethical and conceptual dilemmas we encountered. Impairments may assist rapport building with participants, but also introduce complex dilemmas concerning whether, when and how to disclose them, and the consequences of doing so. We highlight the centrality of the visibility of the disabled body in mediating these dilemmas, and its part in constraining our responses to them. While we value our commitment to positive readings of disability, we demonstrate that disabled researchers nevertheless undertake research in contexts where disability is assigned meanings disabled people may not share. We argue that all researchers should attend to their own ‘body signifiers’ (whether in relation to ethnicity, wealth, gender, age etc.) and embodied experiences of research processes, as these are integral to research outcomes, the ethics of research, and are a means by which to address power differentials between researcher and participant. This paper addresses a gap in the literature, using our experiences of research to highlight the negotiations and dilemmas faced by visibly disabled researchers. Negotiations of identity prompted by the disabled body in the research process require consideration and should not be ignored.